Mechanistic studies on the role of CHI3L1 in eosinophilic inflammation in chronic sinusitis - Guo, Ling; Peng, Yi; Yang, Cheng; Liu, Xinghong; Xiong, Weilan; Liao, Weijiang; Fan, Jiangang (Frontiers in Immunology, 2025)
More than 10% of adults suffer from chronic rhinosinusitis (CRS), a chronic inflammatory condition that lowers quality of life, reduces productivity, and shortens work hours. Every year, more than 1 million surgeries are performed worldwide as a result of CRS. In recent years, targeted therapy for CRS has become a hotspot of research at home and abroad and has made significant progress, but CRS still has a high recurrence rate. Therefore CRS urgently needs precise targeted therapy. In the pathological process of CRS, the involvement of eosinophils is an important inflammatory mechanism. And excessive aggregation of eosinophils often leads to severe inflammatory responses. Studies have shown that chitinase 3-like protein 1 (CHI3L1) plays a key role in the activation and migration of eosinophils. This review will combine the latest research results to analyse in detail the biological properties of CHI3L1, its expression pattern in CRS, and the possible mechanisms by which it affects eosinophil aggregation by regulating immune responses and inflammatory processes, which will provide insights into the key role of CHI3L1 in the pathological process of CRS and offer a new target for the treatment of CRS.